Thrombosis in COVID‐19. Issue 12 (16th September 2020) - Hanff, Thomas C.; Mohareb, Amir M.; Giri, Jay; Cohen, Jordana B.; Chirinos, Julio A.
Abstract: Thrombotic complications are frequent in COVID‐19 and contribute significantly to mortality and morbidity. We review several mechanisms of hypercoagulability in sepsis that may be upregulated in COVID‐19. These include immune‐mediated thrombotic mechanisms, complement activation, macrophage activation syndrome, antiphospholipid antibody syndrome, hyperferritinemia, and renin‐angiotensin system dysregulation. We highlight biomarkers within each pathway with potential prognostic value in COVID‐19. Lastly, recent observational studies have evaluated a role for the expanded use of therapeutic anticoagulation in COVID‐19. We review strengths and weaknesses of these studies, and we also discuss the hypothetical benefit and anticipated challenges of fibrinolytic therapy in COVID‐19.